Imperial China and its southern neighbours - Kelley, Liam C.; Mair, Victor H., d 1943- e editor (Institute of Southeast Asian Studies, 2015)
"At a time when China-Southeast Asia relationships are undergoing profound changes, it is pleasing to have a volume which examines the interactions between China and the polities and societies to the south through time. With multiple aims of exploring the relations between northern Chinese cultures and those of the south, examining the cultural plurality of areas which are today parts of Southern China, and illuminating the relations between Sinitic and non-Sinitic societies, the volume is broad in concept and content. Within these extensive rubrics, this edited collection further interrogates the nature of Asian polities and their historiography, the constitution of Chineseness, imperial China's southern expansions, cultural hybridity, economic relations, regional systems and ethnic interactions across East Asia. The editors Victor H. Mair and Liam C. Kelley are to be congratulated for bringing together such a wealth of contributions offering nascent interpretations and broad overviews, set within the overarching historical and contemporary contexts provided through Wang Gungwu's introduction." -- Dr Geoffrey Wade, ANU College of Asia and the Pacific, Australian National University